2003
DOI: 10.1161/01.cir.0000051459.74466.46
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Increases Vascular Superoxide via Endothelin A –NADPH Oxidase Pathway in Low-Renin Hypertension

Abstract: Background-Angiotensin II-induced hypertension is associated with NAD(P)H oxidase-dependent superoxide production in the vessel wall. Vascular superoxide level is also increased in deoxycorticosterone acetate (DOCA)-salt hypertension, which is associated with a markedly depressed plasma renin activity because of sodium retention. However, the mechanisms underlying superoxide production in low-renin hypertension are undefined. Methods and Results-This study investigated (1) whether and how endothelin-1 (ET-1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
269
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(289 citation statements)
references
References 54 publications
13
269
2
5
Order By: Relevance
“…sympathetic ganglia; phorbol ester; reduced nicotinamide adenine dinucleotide phosphate oxidase; hypertension; deoxycorticosterone acetate VASCULAR ENDOTHELIAL CELLS, smooth muscle cells, and fibroblasts generate reactive oxygen species (ROS), such as O 2 Ϫ ⅐ and H 2 O 2 . ROS play critical roles in both normal and pathophysiological states of vascular cells, including the modulation of redox-sensitive signaling pathways and gene expression, or in the pathophysiology of hypertension and atherosclerosis (16,22,26,36). Several models of hypertension are associated with an increase in vascular O 2 Ϫ ⅐ (41, 42), and this increased O 2 Ϫ ⅐ may quench the endogenous vasodilator nitric oxide (NO) to cause a loss of NO bioactivity in the vessel wall and impair the endothelium-dependent vasorelaxation, resulting in hypertension (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…sympathetic ganglia; phorbol ester; reduced nicotinamide adenine dinucleotide phosphate oxidase; hypertension; deoxycorticosterone acetate VASCULAR ENDOTHELIAL CELLS, smooth muscle cells, and fibroblasts generate reactive oxygen species (ROS), such as O 2 Ϫ ⅐ and H 2 O 2 . ROS play critical roles in both normal and pathophysiological states of vascular cells, including the modulation of redox-sensitive signaling pathways and gene expression, or in the pathophysiology of hypertension and atherosclerosis (16,22,26,36). Several models of hypertension are associated with an increase in vascular O 2 Ϫ ⅐ (41, 42), and this increased O 2 Ϫ ⅐ may quench the endogenous vasodilator nitric oxide (NO) to cause a loss of NO bioactivity in the vessel wall and impair the endothelium-dependent vasorelaxation, resulting in hypertension (26).…”
mentioning
confidence: 99%
“…II-infused rats (24) and in DOCA-salt hypertensive rats (42) can be reversed by antioxidant enzyme, endothelial NO synthase (34), or superoxide dismutase (26). ROS can also induce the expression of cardiovascular-related genes, such as those for adhesion molecules and vasoactive substances.…”
mentioning
confidence: 99%
“…ET-1 increases oxidative stress through the activation of NAD(P)H oxidase-a key enzymatic source for superoxide anion in the vascular wall. 12,13,16,27 Excessive oxidative stress activates several redox-sensitive signalling pathways resulted in activation of MAP kinase family, tyrosine kinases, transcription factors nuclear factor kB, activator protein-1, vascular cellular adhesion molecule-1 and increase release of proinflammatory cytokines. 8,13,26,28,29 The contribution of ET-1, NAD(P)H oxidase and reactive oxygen species in VSMC proliferation was confirmed by the possibility of blocking this process by pre-incubation of VSMC with ET A receptor antagonist, 13 NAD(P)H oxidase inhibitor 12,16 or with antioxidants; 12,13,16 however, it was documented for extracellular superoxide dismutase, 13 and among the antioxidants included in FRAP for ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,16,27 Excessive oxidative stress activates several redox-sensitive signalling pathways resulted in activation of MAP kinase family, tyrosine kinases, transcription factors nuclear factor kB, activator protein-1, vascular cellular adhesion molecule-1 and increase release of proinflammatory cytokines. 8,13,26,28,29 The contribution of ET-1, NAD(P)H oxidase and reactive oxygen species in VSMC proliferation was confirmed by the possibility of blocking this process by pre-incubation of VSMC with ET A receptor antagonist, 13 NAD(P)H oxidase inhibitor 12,16 or with antioxidants; 12,13,16 however, it was documented for extracellular superoxide dismutase, 13 and among the antioxidants included in FRAP for ascorbic acid. 12,16 It was also shown that vitamin C inhibited activation of mitogen-activated protein kinase and VSMC proliferation in cultured rat aortic smooth muscle cells, 26 and in an in vivo experiment it was demonstrated that vitamin C supplementation decreased activation of NADPH oxidase and superoxide anion generation, prevented vascular hypertrophy and increased plasma total antioxidant status and superoxide dismutase in arterial wall in stroke-prone spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation